2017
DOI: 10.1016/j.jaridenv.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Empty Gonometa postica cocoons function as nest sites and shelters for arboreal ants

Abstract: Highlights • Arboreal ants of different species were observed sharing trees and cocoons. • Ants prefer wider cocoons containing small holes in trees containing scale insects. • Ant abundance was lower in cocoons occupied by other invertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…2008, Raath et al . 2017, Seymour & Joseph 2019) and provide a plentiful and reliable food source for breeding Kalahari animals, including the moth and butterfly larvae (e.g. Gonometa postica ) Southern Pied Babblers favour for feeding young (Campbell et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2008, Raath et al . 2017, Seymour & Joseph 2019) and provide a plentiful and reliable food source for breeding Kalahari animals, including the moth and butterfly larvae (e.g. Gonometa postica ) Southern Pied Babblers favour for feeding young (Campbell et al .…”
Section: Discussionmentioning
confidence: 99%
“…Given the early-season foraging behaviour we have observed, it is likely that this resource is associated with camelthorn trees. Irruptive herbivorous invertebrates feed on the new leaf growth, flowers and fruits produced by camelthorn trees during August and September (Steenkamp et al 2008, Raath et al 2017, Seymour & Joseph 2019 and provide a plentiful and reliable food source for breeding Kalahari animals, including the moth and butterfly larvae (e.g. Gonometa postica) Southern Pied Babblers favour for feeding young (Campbell et al 2013, Ridley 2016.…”
Section: Discussionmentioning
confidence: 99%
“…These new habitats might persist on plants and can be later used as shelter by other arthropods in a facilitative interaction process (Vieira and Romero 2013, Cornelissen et al 2016, Zuo et al 2016, Novais et al 2018). Particularly, ants can take advantage of the abandoned shelters made by other insects for nesting, such as wood‐boring beetle abandoned cavities (Tschinkel 2002, Satoh et al 2016, Novais et al 2017), senescent galls (Fernandes et al 1988, Mehltreter et al 2003, Almeida et al 2014, Santos et al 2017, 2019), and empty cocoons (Raath et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the role of caterpillars, gall-inducing insects, and bark and wood-boring beetles as facilitators for arthropods ( Vieira and Romero 2013 , Cornelissen et al 2016 , Harvey et al 2016 , Satoh et al 2016 , Sydenham et al 2016 , Wetzel et al 2016 , Zuo et al 2016 , Raath et al 2017 ). Particularly, when adult wood-boring beetles emerge from tree hosts, they leave behind cavities where their larvae develop, thus promoting new habitats for other species to occupy ( Buse et al 2008 , Zuo et al 2016 ).…”
mentioning
confidence: 99%